CURVATURE DUCTILITY OF UNCONFINED REINFORCED HIGH-STRENGTH CONCRETE BEAM SECTIONS - Cihanli, Ercan; Arslan, Guray (YILDIZ TECHNICAL UNIV, 2009)
Energy absorption capacities of reinforced concrete structural members depend on the level of ductility which can be defined in various ways. Among those, section curvature ductility is one of the most important measures of energy absorption capacities. In this study, unconfined reinforced high-strength concrete beam sections have been considered separately and a computer code has been developed for analyzing each case. Major parameters are the strengths of concrete, yield strength of steel and tensile reinforcement ratio. The change of section curvature ductility with the major parameters has been analyzed using the developed code.
Keywords: Reinforced concrete; beams; ductility; high-strength concrete; reinforcement ratio; Engineering